Metode Pembelajaran Melalui Media Loose Part dalam Meningkatkan Kemampuan Kreatifitas Anak Usia Dini - Dwi Febrianti, Elluza; Ridlwan, Muhammad; Abidin, Ratno (Universitas Muhammadiyah Surabaya, 2023)
The aim of this research is to determine the application of learning methods through loose part media in improving the creative abilities of young children at Dharma Wanita Kedungsari Kindergarten. This research method is quantitative research with a descriptive and inferential approach. The population in this research is TK Dharma Wanita Bendung. Sampling was carried out using the purposive sampling method. Data collection techniques were carried out by distributing pretests and posttests to students before and after learning. The research method used to test the hypothesis was with the help of SPSS software version 16.00 for Windows. The results of the research show that the application of learning methods through loose part media and the dependent variable is the creativity ability of early childhood students at Dharma Wanita Kedungsari Kindergarten in accordance with the data found that the significance of Sig. (2-tailed) is 0.000 < 0.05, then Ho is rejected and Ha is accepted, so it can be concluded that there is an average difference between pre-test and post-test learning outcomes, which means there is an application of learning methods through loose part media. So in this data analysis it can also be seen that the t count has a negative value of 34,568. The t-count has a negative value because the average pretest learning score is lower than the average posttest learning result so that the t-count becomes t-count 34,568 > t-table 2,037, so this means as a basis for decision making that Ho is rejected and Ha is accepted, so it can be concluded that there is a difference between the pretest and posttest averages.